2013
DOI: 10.1155/2013/519341
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous Lipoma of the Sphenoid: A Case Study

Abstract: Intraosseous lipoma is very rare, usually benign tumor of flat bones. However, the localization in skull bones is described in sporadic cases. The differential diagnosis includes end stage of infection, infarct lesions, intraosseous meningioma, angiolipoma, or myxofibrous tumors. We report a patient with intraosseous lipoma located in the sphenoid bone. The diagnosis was established due to the characteristic radiological features. According to the history of seizures, the lesion was removed via endoscopic endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…To date, 18 cases of solitary IOLs involving the calvaria and cranial base have been reported in the literature. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Twelve cases, including our case, evolved from the calvaria, whereas seven cases evolved from the cranial base. The median ages of onset and diagnosis were 3 and 26.5 in calvarial IOLs and 37.5 each in IOLs of the cranial base; the calvarial cases were observed at a younger age.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 18 cases of solitary IOLs involving the calvaria and cranial base have been reported in the literature. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Twelve cases, including our case, evolved from the calvaria, whereas seven cases evolved from the cranial base. The median ages of onset and diagnosis were 3 and 26.5 in calvarial IOLs and 37.5 each in IOLs of the cranial base; the calvarial cases were observed at a younger age.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis needed to exclude the following patologies: meningoencefalocele [13] , intradiploic arachnoid cyst [14] , intradiploic dermoid or epidermoid tumor [15] , intraosseous lipoma [16] . Meningoencefalocele presents as a combination of fluid-filled cyst and parenchyma, which, unlike tumor tissue, isn’t enhanced by the contrast agent; moreover in three-dimensional MRI reconstructions it is possible to note continuity between intracranial brain parenchyma and herniated parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is suggested that, if this process is interrupted, persistence of fatty converted marrow results in the appearance called “arrested pneumatization.” The suggested diagnostic criteria of the arrested pneumatization are a nonexpansile lesion located in the area of normal pneumatization with fatty content, and sclerotic, well‐defined margins . Some authors refer to the lesions as “intraosseous lipoma of the sphenoid.” However, the term “intraosseous lipoma” represents a benign bone neoplasm that contains proliferating mature adipocytes within the normal trabecular bone, such as elsewhere in the skeleton . There are a few cases reported in the literature that had an expansile mass with internal calcifications in the sphenoid bone and fits the term “intraosseous lipoma.” Our patients had nonexpansile or slightly expansile lesions with fat density or intensity and well‐defined margins in adjacent to normal pneumatization areas of sphenoid sinus.…”
Section: Discussionmentioning
confidence: 99%
“…2 Some authors refer to the lesions as "intraosseous lipoma of the sphenoid." 1,5,6 However, the term "intraosseous lipoma" represents a benign bone neoplasm that contains proliferating mature adipocytes within the normal trabecular bone, such as elsewhere in the skeleton. 7 There are a few cases reported in the literature that had an expansile mass with internal calcifications in the sphenoid bone and fits the term "intraosseous lipoma."…”
Section: Discussionmentioning
confidence: 99%